Approach to determine the diversity of Legionella species by nested PCR-DGGE in aquatic environments - Huang, Wen-Chien (PLoS One, 2017)
In this study, we describe a nested PCR-DGGE strategy to detect Legionella communities from river water samples. The nearly full-length 16S rRNA gene was amplified using bacterial primer in the first step. After, the amplicons were employed as DNA templates in the second PCR using Legionella specific primer. The third round of gene amplification was conducted to gain PCR fragments apposite for DGGE analysis. Then the total numbers of amplified genes were observed in DGGE bands of products gained with primers specific for the diversity of Legionella species. The DGGE patterns are thus potential for a high-throughput preliminary determination of aquatic environmental Legionella species before sequencing. Comparative DNA sequence analysis of excised DGGE unique band patterns showed the identity of the Legionella community members, including a reference profile with two pathogenic species of Legionella strains. In addition, only members of Legionella pneumophila and uncultured Legionella sp. were detected. Development of three step nested PCR-DGGE tactic is seen as a useful method for studying the diversity of Legionella community. The method is rapid and provided sequence information for phylogenetic analysis.